O ENSINO DE CIÊNCIAS E A DIVULGAÇÃO CIENTÍFICA NAS ESCOLAS DE ENSINO FUNDAMENTAL EM SÃO LUÍS: O CASO DO RECONHECIMENTO DA LEISHMANIOSE VISCERAL - Lima, Maria Eliana Alves (2007)
Prospectivo study of the conditions and methods of the education of science in schools of basic education in São Luís as form of recognition between pupils of Leishmaniose American Visceral (LVA), problem of endemic health in the island of Is Luis with prevalence in children in the pertaining to school etária band. It is focused necessity of contribution of the school for the clarification of the community on the control of the illness. The research had as objective to verify if the education of sciences in the schools of basic education contributes for the recognition, between pupils, of leishmaniose visceral. The study it was carried through in the Island of São Luís, in the localities of Cidade Olímpica, the city of Are Luis and Vila Bom Viver in the City of Raposa as endemic areas for collection of data and the quarters of Alemanha and Centro in the City of São Luís, as control areas. Five schools of the municipal public net had been selected, being 3 in endemic area and 2 in not endemic area, for application of questionnaires halfstructuralized between the pupils of 3ª and 7ª series of basic education with questions on recognition of the epidemiologia of the LVA and on partner-economic aspects of the pupils. Tests of Qui-Square (x2) of independence had been applied to analyze the differences in the level of knowledge on the LVA in the searched schools. The result analysis showed that it did not have significant difference in the answers of the two areas with regard to the knowledge of the LVA (x2 = 0,886), as well as on its transmission (x2 1,904); in the questions on the form of knowledge on illness only 4.4% of the pupils in endemic area and 3.8% in not endemic area they affirm to have heard to speak on the LVA in the science lessons; however in the two areas it did not have reply difference on the learning by means of the science lesson (x2 = 0,007). The school is concluded exactly that it does not have significant difference in the knowledge of the pupils of endemic and not endemic area on the LVA and that the lessons of sciences are not contributing for the recognition of the illness, when if it finds in a community of endemic area, that, therefore, it possess greater contact with the problematic one.